The Sustainable Glamping Experiencescape: Exploring Visitor Experience and Environmental Awareness - Ghaziana Zhafarini; Kurniawan Saefullah; Yunus Winoto (Eduvest - Journal of Universal Studies, 2025)
Tourism managers and the government are constantly striving to monitor and encourage every tourism activity to adhere to reasonable limits and principles of sustainable tourism. On the other hand, the pandemic has reshaped people's travel preferences, particularly due to numerous digital changes and a wider choice of attractions and activities that are no longer concentrated in cities. People are increasingly venturing out of their homes in safer and more comfortable ways, often choosing natural outdoor spaces as their destinations. This research aims to explore tourist experiences within the context of the sustainable glamping experiencescape, using Bobocabin West Java as the case study. The analysis focuses on natural, functional, social, sensory, and cultural dimensions. The research employed a literature review and in-depth interviews with 10 visitors categorized as solo travelers, family travelers, and group travelers. Data were analyzed using an open coding approach to identify relevant thematic patterns. Findings reveal that natural landscapes serve as the main attraction, distinguishing glamping from conventional accommodations, complemented by modular facilities and smart technologies that enhance comfort. Social aspects, such as friendly service and safety assurance, alongside the inclusion of local SMEs and cultural representation, enriched visitor experiences. Nonetheless, limitations remain in communicating sustainability agendas, accessibility, and the availability of communal spaces. These results underscore the importance of managing glamping through comprehensive sustainability principles to deliver economic, social, and environmental benefits while enhancing tourism competitiveness.